A Preliminary Report on Fluoride Content in Ground Waters of Vallioor Union, Tirunelveli District, Tamil Nadu, India - Santhi, D.; Umayoru Bhagan, V.; Lakshmana Sarma, R. (Asian Journal of Chemistry, 2010)
Ground water is one of the major sources for drinking water in many parts of Vallioor Union. A survey was conducted in these villages by a specially prepared questionnaire. This survey reveals the fact that majority of the residents of these villages were affected by fluorosis. The primary aim of this survey was to find out the concentration of fluoride in the samples of drinking water. Monthly changes in physico-chemical parameters such as temperature, pH, electrical conductivity, total alkalinity, total hardness, calcium, magnesium, fluoride, sodium, sulphate, chloride and salinity were recorded by means of collecting thirty six samples of drinking water from different parts of these areas.